Are the Netherlands a Nordic Country? Reflections on Understanding the Lutheran Tradition in the Netherlands - Hiebsch, Sabine (Nordlit, 2019)
Contrary to the German Lands and the Nordic Countries the Lutherans in the Netherlands were always a religious minority under a non-Lutheran authority. The history of the Dutch Lutherans is closely related to the migration streams of the 16th and 17th century, especially from the German Lands and the Nordic Countries. But the Nordic countries have barely been considered in the historiography of Dutch Lutheranism. This article shows that the relations between the Netherlands and the Nordic Countries happened on a variety of levels. Even though the confessional motivation wasn’t always paramount, this Northern dimension had a decisive influence on the development of Dutch Lutheranism and provides an excellent comparative context to study it. In order to understand its place in the Dutch religious landscape and within the broader context of global Lutheranism, research on the role of the Nordic countries is indispensable.